Causativity and support verb constructions in Latin: the case of "poena afficere" - Mendózar Cruz, Juan (Cuadernos de Filología Clásica. Estudios Latinos, 2015)
In this paper our propose is to analyze the Latin collocation poena afficere, ‘to inflict punishment’, a type of collocation having both syntactic and semantic specificities that distinguish it from the prototypical ones: the predicative noun functions as third argument of the support verb, a syntactic scheme that is ideal, as we shall attempt to demonstrate, for the expression of causative predicates. From the examples of poena afficere documented in a large text corpus, we will intend to highlight the main features of this type of collocation. For its description and formalization, we will use the theoretical framework proposed by the Meaning-Text Theory.
Keywords: Poena; Afficere; Latin; Support verb; Causativity; Meaning-Text Theory.